Investigating the Causal Relationship between Family Affective Atmospheres and Academic Self-Handicapping with Academic Dishonesty: The Mediating Role of Academic Self-Concept in Secondary School Students in Khorramabad - Abdalmohammad Ordozadeh; Farah Naderi; Zahra Eftekhari Saadi,; Parvin Ehteshamzadeh, (پژوهش‌های کاربردی روانشناختی)
The aim of this study was to investigate the mediating role of academic self-concept in the relationship between family affective atmospheres and academic self-handicapping and academic dishonesty in secondary school pupils in Khorramabad. In this correlational study, the iterative cluster sampling method was employed to select 300 secondary school students in Khorramabad city during the academic year 2021-2022. In this study, Family affective atmospheres (FEAQ), Academic self-handicapping (ASHQ), Academic dishonesty (ADQ) and Academic self-concept (ASCQ) were used for data collection in this study. The path analysis method and SPSS-27 and AMOS-25 software were employed to evaluate the proposed model. The results showed that all direct paths, with the exception of the family affective atmospheres path and academic dishonesty, were statistically significant (p<0.05). Also, significant familial affective atmospheres and academic self-handicapping were indirect pathways with academic dishonesty, with academic self-concept mediating the relationship (p=0.05). According to the findings of this study, the proposed model has a good fit and is an important step in identifying the factors affecting students’ academic dishonesty.